Diagnostic value of neutrophil to lymphocyte ratio in differentiation of ruptured ovarian cysts and adnexal torsion - TEMOÇİN, REZZAN BERNA; SOYSAL, SUAH (GALENOS YAYINCILIK, 2018)
Objective: Ovarian cyst rupture and adnexal torsion (AT) differential diagnosis is important for early surgical intervention of AT for preserving ovarian function. The aim of this study was to evaluate the diagnostic value of preoperative the neutrophil-to-lymphocyte ratio (NLR) in patients with adnexal torsion and ovarian cyst rupture. Materials and Methods: Data of 80 patients who underwent surgery between 2012 and 2017 for ovarian cyst rupture, adnexal torsion, and unruptured ovarian cyst were analyzed. Patients were categorized as adnexal torsion (n=35), ovarian cyst rupture (n=20), unruptured ovarian cyst (n=25) groups. Preoperative NLR were compared among the three groups of the patients. Results: The adnexal torsion group had a median NLR of 8.0 (range, 4.0-14.1), the ovarian cyst rupture group had a median of NLR 7.5 (range, 3.7-11.5), and median NLR of the unruptured ovarian cyst group was 2.2 (range, 1.8-2.7). The NLR was found to have a difference that reached statistical significance among the three groups (p<0.001). When the groups were individually compared, there was no significant difference between the ovarian cyst rupture and adnexal torsion groups (p=0.372), but there was a significant difference between the unruptured ovarian cyst and adnexal torsion groups (p<0.001). Conclusion: NLR may be useful in the differential diagnosis of unruptured ovarian cyst from adnexal torsion, but it has no diagnostic value for the differentiation of ovarian cyst rupture and adnexal torsion.
Keywords: Adnexal torsion; ovarian cyst; rupture; neutrophil; lymphocyte; MEAN PLATELET VOLUME; PREDICTOR; NEUTROPHIL/LYMPHOCYTE; MANAGEMENT; SEVERITY; CHILDREN; DISEASE